Death and taxes and pensions - Stuart Adam; Isaac Delestre; Carl Emmerson; David Sturrock (Institute for Fiscal Studies (IFS), 2022)
The tax system treats funds that remain in a pension at death extremely favourably. Where an individual dies before age 75, funds remaining in their pension escape income tax entirely - there was income tax relief when the money was paid into the pension and no income tax when the money is taken out. Furthermore, any funds that remain in a pension at death (at any age) are not subject to inheritance tax. This results in the bizarre situation where pensions are treated more favourably by the tax system as a vehicle for bequests than they are as a retirement income vehicle. As such, there is a large incentive, for those who can, to use non-pension assets to fund their retirement while preserving their pensions for bequests. This report sets out some options for a more coherent tax treatment of funds that remain in a pension at death. The reforms we propose, potentially with some transitional arrangements, would make the tax system fairer and more economically efficient. The revenue raised by moving to a more sensible system, even if relatively modest in the near term, could be substantial in the longer term. This revenue could be used to cut taxes elsewhere - including income tax and inheritance tax - or to ease the planned squeeze on public spending.
Keywords: 330; Savings; pensions and wealth; Taxes and benefits; Income taxes; Tax; Private pensions; Taxes on wealth and spending; Wealth